Associated factors with parental pregnancy decision-making and use of consultation after a prenatal congenital heart disease diagnosis - Wan-Ling Chih; Yu-Hsuan Tung; Eric C. Lussier; Chan-Yu Sung; Yi-Ling Huang; Wei-Li Hung; Kang-Hong Hsu; Chung-I Chang; Tung Yao Chang; Ming-Ren Chen (Pediatrics and Neonatology)
Background: Prenatal diagnosis of congenital heart disease (CHD) often leads affected families to experience psychological stress. Pediatric cardiology consultation is important in providing parents with sufficient information and reducing their anxiety to make an informed pregnancy decision. Involving a fetal nurse coordinator may optimize fetal anomaly care. Our study aimed to identify factors associated with parental decision-making for choosing to use pediatric cardiology consultations and pregnancy termination. Methods: From September 2017 to December 2018, all fetal CHD cases diagnosed in the second trimester from a primary screening clinic in Taiwan were included (n = 145). Univariate and multivariate logistic regression were performed to analyze maternal, fetal, and medical factors for predictors of parental decisions for consultation use and pregnancy termination. Results: Acceptance for fetal nurse coordinator care and pediatric cardiology consultation were 84.8% (n = 123) and 83.4% (n = 121), respectively. Predictors for termination of pregnancy included the following: multiple anomalies (OR: 10.6; 95% CI: 3.6–35.7), chromosomal/genetic abnormalities (OR: 20.2; 95% CI: 3.1–395.8), severe CHDs (OR: 9.8; 95% CI: 4.3–23.4), CHDs that required surgery (OR: 32.4; 95% CI: 11.4–117.8), and physiological single-ventricle (OR: 47.3; 95% CI: 12.4–312.5). Parents who had pediatric cardiology counseling were less likely to terminate the pregnancy (OR: 0.1; 95% CI: 0.0–0.7). Parents with fetal diagnosis having multiple anomalies (OR: 0.2; 95% CI: 0.1–0.7) or chromosomal/genetic abnormalities (OR: 0.1; 95% CI: 0.03–0.9) were less likely to make use of cardiology consultation. Parents who accepted fetal nurse coordinator care were more likely to have pediatric cardiology consultation before pregnancy decision (OR: 149.5, 95% CI: 37.8–821.5). Conclusions: Anomaly complexity appeared to be a strong predictor for termination of pregnancy beyond non-acceptability of prenatal cardiology consultation. Prenatal cardiology counseling may help support the parental decision to continue with the pregnancy. Incorporation of a fetal nurse coordinator care into the multidisciplinary fetal medicine team improved the acceptability of prenatal consultation.